2020
DOI: 10.1186/s12939-020-01223-2
|View full text |Cite
|
Sign up to set email alerts
|

The safety of health care for ethnic minority patients: a systematic review

Abstract: Introduction: Evidence to date indicates that patients from ethnic minority backgrounds may experience disparity in the quality and safety of health care they receive due to a range of socio-cultural factors. Although heightened risk of patient safety events is of key concern, there is a dearth of evidence regarding the nature and rate of patient safety events occurring amongst ethnic minority consumers, which is critical for the development of relevant intervention approaches to enhance the safety of their ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
172
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 151 publications
(175 citation statements)
references
References 78 publications
3
172
0
Order By: Relevance
“…Furthermore, the quality of the population’s access to primary healthcare and the optimization of the service performance could be determining factors [ 73 , 74 , 75 ] as it could prevent people being admitted to a hospital with greater vulnerability and a higher risk of susceptibility to infection. Another important factor is related to socio-economic and racial factors; there are already a few studies in which these factors have been found to be significant in association with patients who acquire an infection after an extended stay in hospital [ 76 , 77 ]. In a prospective investigation, it may be useful to cross-reference data on the consumption of antibiotics, disaggregated at the municipal scale, with the highest spatial incidence of HAIs, also controlling for the origin of the patients, specifically whether they come from their own dwelling or if they are residents in nursing homes, where the level of previous infections and antibiotic use is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the quality of the population’s access to primary healthcare and the optimization of the service performance could be determining factors [ 73 , 74 , 75 ] as it could prevent people being admitted to a hospital with greater vulnerability and a higher risk of susceptibility to infection. Another important factor is related to socio-economic and racial factors; there are already a few studies in which these factors have been found to be significant in association with patients who acquire an infection after an extended stay in hospital [ 76 , 77 ]. In a prospective investigation, it may be useful to cross-reference data on the consumption of antibiotics, disaggregated at the municipal scale, with the highest spatial incidence of HAIs, also controlling for the origin of the patients, specifically whether they come from their own dwelling or if they are residents in nursing homes, where the level of previous infections and antibiotic use is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…There is emerging evidence identifying factors that present barriers to CALD consumer engagement, leading to variations in access to and experience of healthcare, and poorer health and healthcare quality outcomes 14,20–22 . A recent systematic review concluded that safety events (events that could have or did result in harm due to care they receive) among CALD patients are dependent on the setting and the population, and that poor engagement with CALD consumers is one factor associated with their increased vulnerability to safety events 23 . Poor engagement is often associated with an inability of the health system to recognise and address the nuanced sociocultural differences that exist between and within diverse CALD groups and with a lack of responsiveness to those differences 14,23 .…”
Section: Introductionmentioning
confidence: 99%
“…Their feedback was discussed between the authors and used to revise the tool iteratively through a series of minor amendments to wording and ordering or the tool items. The resulting QuADS tool was also subject to inter-rater reliability analysis between a psychologist, public health and health services researcher through application to 40 studies a recent systematic review with a kappa of 0.65 published by a colleague within our department who was external to this study [ 15 ].…”
Section: Methodsmentioning
confidence: 99%